Fluopsin C for Treating Multidrug-Resistant Infections: In vitro Activity Against Clinically Important Strains and in vivo Efficacy Against Carbapenemase-Producing Klebsiella pneumoniae - Navarro, Miguel Octavio Pérez; Simionato, Ane Stefano; Pérez, Juan Carlos Bedoya; Barazetti, André Riedi; Emiliano, Janaina; Niekawa, Erika Tyemi Goya; Andreata, Matheus Felipe de Lima; Modolon, Fluvio; Dealis, Mickely Liuti; Araújo, Eduardo José de Almeida; Carlos, Thalita Massi; Scarpelim, Odair José; et al. (Frontiers in Microbiology, 2019)
The increasing emergence of multidrug-resistant (MDR) organisms in hospital infections is causing a global public health crisis. The development of drugs with effective antibiotic action against such agents is of highest priority. In the present study, the action of Fluopsin C against MDR clinical isolates was evaluated, under in vitro and in vivo conditions. Fluopsin C was produced in cell suspension culture of Pseudomonas aeruginosa LV strain, purified by liquid adsorption chromatography and identified by mass spectrometric analysis. Bioactivity, bacterial resistance development risk against clinically important pathogenic strains and toxicity in mammalian cell were initially determined by in vitro models. In vivo toxicity was evaluated in Tenebrio molitor larvae and mice. The therapeutic efficacy of intravenous Fluopsin C administration was evaluated in a murine model of Klebsiella pneumoniae (KPC) acute sepsis, using six different treatments. The in vitro results indicated MIC and MBC below 2 μg/mL and low bacterial resistance development frequency. Electron microscopy showed that Fluopsin C may have altered the exopolysaccharide matrix and caused disruption of the cell wall of MDR bacteria. Best therapeutic results were achieved in mice treated with a single dose of 2 mg/kg and in mice treated with two doses of 1 mg/kg, 8 hours apart. Furthermore, acute and chronic histopathological studies demonstrated absent nephrotoxicity and moderate hepatotoxicity. The results demonstrated the efficacy of Fluopsin C against MDR organisms, in in vitro and in vivo models, and hence it can be a novel therapeutic agent for the control of severe MDR infections.